Supplementary data to Metaldehyde removal from drinking water by adsorption on to filtration media and polymeric sorbents: mechanisms and optimisation - Rolph, Catherine; Jefferson, Bruce; Villa, Raffaella; Hassard, Francis (Cranfield University, 2018)
This study sheds light into adsorption of metaldehyde to different polymeric sorbents. Biologically active carbon had the greatest metaldehyde adsorption capacity. Natural organic matter reduced metaldehyde removal in competitive sorption environments. We theorized that microbial biofilms and thermal hydrolysis represent effective strategies for improving metaldehyde removal and reducing the rapid saturation of filtration media.
Keywords: biofilm biomass'; 'Natural Organic Matters'; 'pesticides'; 'metaldehyde decomposition'; 'adsorbents show improvement'; 'Water Treatment Processes'